Normal Th1 development following long-term therapeutic blockade of CD154-CD40 in experimental autoimmune encephalomyelitis - Howard, Laurence M. (American Society for Clinical Investigation, 2002)
Experimental autoimmune encephalomyelitis (EAE) is a Th1-mediated demyelinating disease of the CNS with similarities to multiple sclerosis. We and others have shown that a short-term course of anti-CD154 mAb treatment to block CD154-CD40 interactions can be used to prevent or even treat ongoing PLP139-151–induced relapsing EAE. However, little is known of the long-term effects of CD154 blockade on the development of antigen-specific T cell function. Here, we show that short-term treatment with anti-CD154 at the time of PLP139-151/CFA immunization inhibits clinical disease for up to 100 days after immunization. At this point, comparable numbers of Th1 cells are observed in anti-CD154 and control Ig–treated mice, as assessed by antigen-specific ELISPOT assays. Thus, the long-term Th1/Th2 balance is largely unaffected. Inflammatory responses are diminished in anti-CD154–treated mice, as indicated by reduced in vivo delayed-type hypersensitivity and reduced levels of splenic IFN-γ secretion in vitro. However, upon adoptive transfer of T cells isolated from the spleens of anti-CD154–treated mice, these cells contributed as effectively to clinical disease as those obtained from control-treated mice. Thus, anti-CD154 therapy leads to long-term therapeutic efficacy without exerting a long-term influence on Th1 development.